Prevalence and Associated Factors of Emotional Intelligence Among Nursing Students of a Tertiary Level Medical College - Shrestha, Srijana; Upadhyay, Hari Prasad (Journal of National Heart and Lung Society Nepal, 2026)
Background: Emotional intelligence (EI) is the ability to recognize, understand, manage, and effectively use emotions in oneself and others. It is an important competency for nursing students as it contributes to effective communication, empathy, stress management, and quality patient care. The objective of this study is to assess the prevalence of emotional intelligence and its associated factors among nursing students. Methods: An analytical cross-sectional study was conducted among nursing students at a Teaching Hospital of Bharatpur, Chitwan. Data were collected using a self-administered structured questionnaire. The data were entered and analyzed using SPSS version 20. Descriptive and inferential statistics were used to summarize the findings and examine associations between emotional intelligence and selected socio-demographic variables. P-value<0.05 was considered statistically significant. Results: The majority of respondents were aged 18–19 years (44.8%), unmarried (95.7%), and had chosen nursing of their own interest (94.0%), 78.4% of the students demonstrated a high level of emotional intelligence. Academic year showed association with emotional intelligence (p=0.071). Conclusion: Most nursing students had a high level of emotional intelligence. Although socio-demographic factors showed limited influence, emotional intelligence appeared to increase with academic progression. Integrating emotional intelligence development into nursing education may help strengthen students’ professional competencies and improve patient care outcomes.